Information and documentation for banana and plantain In East Africa - a report on a regional workshop - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Information and documentation for banana and plantain In East Africa - a report on a regional workshop held in Bujumbura, Burundi, 18-23 June, 1990 and sponsored by the International Network for the Improvement of Banana and Plantain (INIBAP), the...